Rediscovering Paul Philemon and the sociology of Paul's narrative world - Petersen, Norman R., 1933- (Philadelphia, PA Fortress, 1985)
Includes bibliographical references and index.
Keywords: Bible. N.T. Philemon -- criticism, interretation, etc; Sociology, Biblical